Poly(ADP-ribose) polymerase activation induces high mobility group box 1 release from proximal tubular cells during cisplatin nephrotoxicity - Kim, J (Physiological research, 2016)
Cisplatin is one of the most potent chemotherapy drugs against cancer, but its major side effect such as nephrotoxicity limits its use. Inhibition of poly(ADP-ribose) polymerase (PARP) protects against various renal diseases via gene transactivation and/or ADP-ribosylation. However, the role of PARP in necrotic cell death during cisplatin nephrotoxicity remains an open question. Here we demonstrated that pharmacological inhibition of PARP by postconditioning dose-dependently prevented tubular injury and renal dysfunction following cisplatin administration in mice. PARP inhibition by postconditioning also attenuated ATP depletion during cisplatin nephrotoxicity. Systemic release of high mobility group box 1 (HMGB1) protein in plasma induced by cisplatin administration was significantly diminished by PARP inhibition by postconditioning. In in vitro kidney proximal tubular cell lines, PARP inhibition by postconditioning also diminished HMGB1 release from cells. These data demonstrate that cisplatin-induced PARP1 activation contributes to HMGB1 release from kidney proximal tubular cells, resulting in the promotion of inflammation during cisplatin nephrotoxicity.
Keywords: protein HMGB1; Acute Kidney Injury; Cisplatin; myši inbrední C57BL; cisplatina; mužské pohlaví; HMGB1 Protein; Mice; Antineoplastic Agents; ledvinové kanálky; protinádorové látky; zvířata; Kidney Tubules; akutní poškození ledvin; myši; Poly (ADP-Ribose) Polymerase-1; poly(ADP-ribosa)polymerasa 1; Mice, Inbred C57BL; Male; Animals